Ultra-barcoding in cacao (Theobroma spp.; Malvaceae) using whole chloroplast genomes and nuclear ribosomal DNA - Nolan K.; Sveinsson, S.; Dempewolf, Hannes; Ji Yong Yang; Dapeng Zhang; Engels, Johannes M.M.; Cronk, Q.C.B. (Wiley, 2012)
• Premise of study: To reliably identify lineages below the species level such as subspecies or varieties, we propose an extension to DNA‐barcoding using next‐generation sequencing to produce whole organellar genomes and substantial nuclear ribosomal sequence. Because this method uses much longer versions of the traditional DNA‐barcoding loci in the plastid and ribosomal DNA, we call our approach ultra‐barcoding (UBC).• Methods: We used high‐throughput next‐generation sequencing to scan the genome and generate reliable sequence of high copy number regions. Using this method, we examined whole plastid genomes as well as nearly 6000 bases of nuclear ribosomal DNA sequences for nine genotypes of Theobroma cacao and an individual of the related species T. grandiflorum, as well as an additional publicly available whole plastid genome of T. cacao.• Key results: All individuals of T. cacao examined were uniquely distinguished, and evidence of reticulation and gene flow was observed. Sequence variation was observed in some of the canonical barcoding regions between species, but other regions of the chloroplast were more variable both within species and between species, as were ribosomal spacers. Furthermore, no single region provides the level of data available using the complete plastid genome and rDNA.• Conclusions: Our data demonstrate that UBC is a viable, increasingly cost‐effective approach for reliably distinguishing varieties and even individual genotypes of T. cacao. This approach shows great promise for applications where very closely related or interbreeding taxa must be distinguished.